Biodegradation of bisphenol-A polycarbonate plastic by Pseudoxanthomonas sp. strain NyZ600 - Yue, Wenlong; Yin, Chao-Fan; Sun, Limin; Zhang, Jie; Xu, Ying; Zhou, Ning-Yi (Journal of hazardous materials, 2021)
Bisphenol-A polycarbonate (PC) is a widely used engineering thermoplastic and its release has caused damage to the ecosystem. Microbial degradation of plastic represents a sustainable approach for PC reduction. In this study, a bacterial strain designated Pseudoxanthomonas sp. strain NyZ600 capable of degrading PC was isolated from activated sludge by using diphenyl carbonate as a surrogate substrate. Within a 30-day period of incubating with strain NyZ600, PC films were analyzed with atomic force microscopy, scanning electron microscope, water contact angle, X-ray photoelectron spectroscopy, fourier transform infrared spectroscopy, differential scan calorimeter and thermogravimetric analysis technique. The analyses results indicated that the treated PC films were bio-deteriorated and formed some “corrosion pits” on the PC film surface. In addition, strain NyZ600 performed broad depolymerization of PC indicated by the reduction of Mn from 23.55 to 16.75 kDa and Mw from 45.67 to 31.97 kDa and two degradation products bisphenol A and 4-cumylphenol (the two monomers of PC) were also found, which established that PC were biodegraded by strain NyZ600. Combing all above results, it is clear that the strain NyZ600 can degrade PC which provides a unique example for bacterial degradation of PC and a feasibility for the removal of PC waste. [Display omitted] •A rapid screening method for PC-degrading bacteria was devolved.•A bacterial strain capable of degrading PC was isolated from activated sludge.•Various analyses showed PC degradation after the treatment of the bacterial strain.•Catabolites bisphenol A and 4-cumylphenol from PC depolymerization were detected.